Tea Consumption and Gut Microbiome in Chinese Men and Women. (14th June 2022) - Wang, Lei; Shu, Xiao-Ou; Cai, Hui; Yang, Yaohua; Xu, Wanghong; Wu, Jie; Cai, Qiuyin; Zheng, Wei; Yu, Danxia
Abstract: Objectives: To evaluate the associations of tea drinking habits with gut microbiome diversity and composition among senior Chinese adults. Methods: Included in the study were 1179 men and 1078 women from the Shanghai Men's Health Study and Shanghai Women's Health Study who were free of cancer, cardiovascular disease, and diabetes at stool collection (2015–2018) and had no diarrhea or antibiotic use in the last 7 days before stool collection. The gut microbiome was profiled by 16S rRNA sequencing. Tea drinking habits were assessed at the cohorts' baseline and follow-up surveys (1996–2011), including status (current or not), type (green tea or others), amount (tertile cutoffs: 2 and 3.3 cups/day in men; 1.3 and 2 cups/day in women), and duration (tertile cutoffs: 30.8 and 41.0 years in men; 15.1 and 32.8 years in women). The associations of tea variables with microbiome diversity and taxa abundance were evaluated by linear or negative binomial hurdle models after appropriate data transformation and adjusting for age, education, income, tobacco smoking, alcohol drinking, physical activity, body mass index, diet quality score, and hypertension status. False discovery rate < 0.1 at each taxonomic level was considered statistically significant. Results: The mean ± SD age at stool collection was 67.2 ± 9.0 years in men and 69.6 ± 8.5 years in women. None of the tea drinking variables showed significant association with microbiome ɑ-diversity in men or women; however, tea drinking status, type, amount, and duration were all significantly associated with β-diversity (Bray–Curtis distance) in men ( P < 0.001). Significant associations with taxa abundance were also observed only in men. Current tea drinking, particularly green tea drinking, was associated with increased abundance of order Synergistales and class Mollicutes and its order RF39 ( P FDR < 0.10). In addition, increased abundance of families Coriobacteriaceae, Odoribacteraceae and genera Collinsella, Odoribacter were observed among men who drank >3.3 cups per day (high amount vs. non-drinkers). Conclusions: Tea drinking may affect gut microbiome β-diversity and abundance of some bacteria in Chinese men. Future studies are needed to examine the potential sex-specific effect of tea drinking on gut microbiome and the role of these bacteria in mediating the health benefits of tea. Funding Sources: The National Institutes of Health.